The glucose sensor protein glucokinase is expressed in glucagon-producing alpha-cells. - Heimberg, H (1996)
Expression of glucokinase in hepatocytes and pancreatic 6-cells is of major physiologic importance to mammalian glucose homeostasis. Liver glucokinase catalyzes the first committed step in the disposal of glucose, and beta-cell glucokinase catalyzes a rate-limiting step required for glucose-regulated insulin release. The present study reports the expression of glucokinase in rat glucagon-producing alpha-cells, which are negatively regulated by glucose. Purified rat alpha-cells express glucokinase mRNA and protein with the same transcript length, nucleotide sequence, and immunoreactivity as the beta-cell isoform. Glucokinase activity accounts for more than 50% of glucose phosphorylation in extracts of alpha-cells and for more than 90% of glucose utilization in intact cells. The glucagon-producing tumor MSL-G-AN also contained glucokinase mRNA, protein, and enzymatic activity. These data indicate that glucokinase may serve as a metabolic glucose sensor in pancreatic alpha-cells and, hence, mediate a mechanism for direct regulation of glucagon release by extracellular glucose. Since these cells do not express Glut2, we suggest that glucose sensing does not necessarily require the coexpression of Glut2 and glucokinase.